Tiger Woods : making of a champion - Garrity, John (Simon & Schuster New YorkUS, 1997)
Traces the progress of Tiger Wood's stellar career from amateur golfer in 1992 at age 16 to his professional exploits in 1997. Illustrates the narrative throughout with photographs of Tiger and the significant players in his life including his parents, admirers, caddy etc. Records his challenges and triumphs, as well as the changes which he has brought to the game.